Plant diversity drives sandy-loam soil quality and crop yields in integrated crop-livestock systems - Gonçalves, Evelyn Custódio; Silva, Laércio Santos; De Camargo, Tatiane Andrea; Nogueira, Bruna Karolayne Andrade; Dalla Côrt, Andressa Selestina [UNESP]; Ponce, Polyana Freitas; Pires, Gabriela Castro; Silva, Izabela Aline Gomes Da; Pacheco, Leandro Pereira; Tadini, Amanda Maria; Martin-Neto, Ladislau; De Moraes, Anibal; et al. (Cambridge University Press (CUP), 2025)
Agricultural monoculture negatively impacts soil quality, particularly in fragile soils that yield limited crop production and are highly susceptible to degradation. Increasing plant diversity in production systems can be an alternative for maintaining soil ecosystem services and increasing crop yields. This study investigated the influence of increased plant diversity on soil health and its impact on soybean and cotton yield in an Ultisol in the Brazilian savanna in Mato Grosso State, Brazil. Tested five levels of plant diversity after soybean harvest: 1) very low (VL), 2) low (LW), 3) average (AVG), 4) long term average (AVL) e 5) high (ICLS) were tested. Plant diversity improves the health of sandy loam soil, increases C and N fractions in particulate organic matter (POM-C and POM-N) and leads to differences in C utilization by the soil microbial community. High ICLS diversity raises total organic carbon levels (TC, being POM-C and POM-N, the labile fractions, more efficient to show changes in sandy loam soil, in the short term, over a period of three years. High diversity promoted yield gains of up to 251% for cotton and 82% for soybean in relation to very low plant diversity. Changes in soil microbial composition are able to partially explain crop yield in diversified production systems (R2 ranging from 0.51 to 0.80). Diversifying production components is a sustainable way to maintain biological functions and agricultural quality of loam sandy soil in the Brazilian Cerrado in Mato Grosso. The Author(s), 2025.
Keywords: agricultural production; fragile soil; Gossypium hirsutum L.; soil health; soil microbiological communities